"An AI doesn't need a gender" (but it's still assigned one): paradigm shift of the artificially created woman in film. Issue 3 (2nd April 2020) - Escudero Pérez, Jimena
ABSTRACT: The artificially created woman has been a recurring trope in narratives since ancient times. Its filmic representation has traditionally been polarized between the submissive "angel in the house" figure of the servant wife, and that of the dangerous evil doll who uses her charms to harm men. In both cases, these characters have always shared a set of features: they were created by and dependent on men, hypersexualized, commodified, powerless and, with honourable exceptions, played secondary and expendable roles. Following the most common norm for any female character, these creatures also had to be completely tamed, or else put to an end. However, the turn of the decade has shown significant transgressions of past stigmas to the point that, I argue, a shift in the paradigm can now be identified. The Machine (2013), Her (2013), Autómata (2014) and Ex Machina (2015) are used here to exemplify this narrative change. The sample also serves to explore issues related to gender construction, human identity itself and the ways in which its merging with technology forces us to question and redefine our own ontology.